Red Mars 2026 - Kim Stanley Robinson (Fanucci Editore, 1992)
John Boone, Maya Toitovna, Frank Chalmers, and Arkady Bogdanov lead a mission whose ultimate goal is the terraforming of Mars in order to release Martian moisture into their desolate atmosphere. Simultaneous.
Droits : Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: Inde; voyage; Kipling; classique; Histoire